Understanding the Implications of Research Skills Development Framework for Indonesian Academic Outcomes Improvement - Prasetyono Hendriarto; Agus Mursidi; Nawang Kalbuana; Nurul Aini; Aslan Aslan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
The qualitative study aimed to understand the Research Skills Development Framework (RSD) implications for Indonesian master students' academic achievement. Experience proves that success at the master's level is closely related to mastering academic research competencies. A typical study at the master's level requires research skills to complete tasks and jobs that require research application acuity. To understand this study's problem, study the data we have done, including reviewing ten academic findings from international publications, observing and documenting data related to this topic. After the data was collected, we were then provided with analysis, including text analysis, description, coding, and immersion results. Every text is in a language, so we use a translation application to help us understand Indonesian. To determine whether the data constitutes a valid and reliable study finding, we review it and make sure we have answered the study questions. So the results we can report that the RSD framework has become a conceptual framework for the development of research skills for academic and educational needs. The reason is that the RSD framework is beneficial and useful in working on completing tasks that require skill in examining problems to find answers. Thus, these findings become meaningful input for the academic community and other professions. Keywords: Research Skill Development, Academic Outcome Improvement, Academic Achievement